Paint-covered alleyway wall and partially-completed sign - Lê Thái Hoàng Nguyên (22638911) (2025)
Close-up shot of the front wall of Artist Thuyên's alleyway home onto which several layers of paint of different colours have transferred while he is painting signs, including the one underneath his hand.